2008
DOI: 10.1007/s11695-007-9279-8
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Roux-en-Y Gastric Bypass Surgery on Morbidly Obese Patients with Hypothyroidism

Abstract: Hypothyroidism appears to improve in the vast majority of morbidly obese patients who undergo LRYGB, except for those whose thyroid disease is autoimmune in nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 18 publications
2
23
1
2
Order By: Relevance
“…The observation that weight loss is associated with decreases in TSH and FT3 has highlighted that TSH elevation may be a consequence and not the cause of obesity [11-16, 18, 19]. Even in patients with a clinical diagnosis of hypothyroidism, there are reports of decreased levels of TSH after bariatric surgery [13,14,26,27]. In two studies, all the patients with untreated subclinical hypothyroidism reached normal values of TSH 12 months after bariatric surgery [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…The observation that weight loss is associated with decreases in TSH and FT3 has highlighted that TSH elevation may be a consequence and not the cause of obesity [11-16, 18, 19]. Even in patients with a clinical diagnosis of hypothyroidism, there are reports of decreased levels of TSH after bariatric surgery [13,14,26,27]. In two studies, all the patients with untreated subclinical hypothyroidism reached normal values of TSH 12 months after bariatric surgery [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…2) [22], where the frequency of underlying thyroid disease in the population is much lower than in adults. Characteristically, weight reduction by change of lifestyle and diet [22,23] or following gastric banding [24] or gastric bypass surgery [25] tends to ameliorate the small aberration in thyroid function tests in the majority of obese patients.…”
Section: Obesity and Pituitary-thyroid Activationmentioning
confidence: 99%
“…The exact mechanism of improvement of thyroid dysfunction status after bariatric surgery related not only to weight loss but also to the hormonal change after LSG, LRYGB as hypothesized by different studies in which the level of TSH reduction was not directly correlated to the EWL [4,8,15].…”
Section: Discussionmentioning
confidence: 98%
“…Fazylov et al [4] have shown a decrease in postoperative L-thyroxine dosage after LRYGB for morbid obese patient with clinical hypothyroidismin 35% of patients (25% complete resolution and 10% reduction in dose) in dose unchanged in 40% of patients and worsened in 25% of patients with thyroid autoimmune disease.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation